Companies adjust tax payments to offset changes in publicly perceived impact on environment, social, and governance factors - Akihiro Okuyama; Shuichi Tsugawa; Chiaki Matsunaga; Shunsuke Managi (Humanities & Social Sciences Communications)
Abstract Corporate tax avoidance is a significant international issue, resulting in annual losses of USD 100–240 billion for governments globally. Understanding the relationship between firms’ corporate social responsibility (CSR) and tax avoidance activities is crucial to uncovering their motivations for tax avoidance. However, this relationship remains unclear. This study investigates firms’ tax payment motivations from environmental, social, and governance (ESG) perspectives by examining samples of firms with high, low, and no ESG-related reputational risk. We utilize the ESG index, which offers a broader scope than conventional CSR measures. Our empirical analysis includes 3981 firm-year observations from 31 OECD countries between 2017 and 2019. To determine the relationship between ESG and tax avoidance, we develop a reputation-based ESG risk dataset that addresses the endogeneity associated with managerial decisions and simultaneity bias. This study is among the few that explore the international relationship between ESG performance and tax avoidance, contributing to the shift from CSR to ESG in discussions of tax avoidance. Our findings reveal that companies’ tax payment behavior varies based on their ESG reputational risk. Specifically, firms with high ESG risk pay more taxes when their ESG risk is elevated, whereas firms with low ESG risk do not alter their tax payments based on ESG risk. Additionally, firms without any ESG risk tend to pay more taxes as their ESG scores increase.